The power of AIPAC (American-Israel Public Affairs Committee) and U.S.- Israel special relationship future of the Palestinian State in the Middle East - Nor Aishah Hanifa (Partridge Publishing, 2020)
The Israeli-Palestinian conflict is a multi-dimensional conflict with numerous forces working collectively from international structure, regional structure and domestic structure. This book aims to offer a comprehensive reading on the AIPAC, the U.S. Middle East Policy, Israel, structural fault lines, and creation of the Palestinian state. The book touches on specific aspects, such as; - The macro dimension of the Israeli-Palestinian conflict. - U.S.-Israel Special Relationship (1948-2019). - The American Jewry. - The AIPAC and its modus operandi in U.S. - The U.S. Middle East Policy. - Future of the Palestinian State in the Middle East.